Sofrimento psíquico do bailarino: um olhar da psicodinâmica do trabalho - Selma Lancman; Marina Petrilli Segnini (Universidade do Porto, 2011)
The present article is part of a series of studies that articulate work and mental health. The aim is to analyze the relationships between the dance workers and the organization of dance as a work in light of the psychodynamic of work theory. This analysis focuses on the way dance workers mobilize their subjectivity while performing their daily work activities in Balé da Cidade de São Paulo (São Paulo City Ballet), a public dance company linked to the Theatro Municipal de São Paulo in Brazil (São Paulo City Theatre). We aimed at understanding the strategies that are subjectively mobilized by the dancers when facing suffering due to work based on a qualitative study conducted through interviews and personal observation of the work process. We concluded that one of the strategies adopted by this group of workers is the quest for a split between the biological body, which is exercised on a technical way and used as a work tool, and the erogenous body, that houses the subjective experiences.